The value of consciousness - Levy, N (Imprint Academic, 2014)
Consciousness, or its lack, is often invoked in debates in applied and normative ethics. Conscious beings are typically held to be significantly more morally valuable than non-consious, so that establishing whether a being is conscious becomes of critical importance. In this paper, I argue that the supposition that phenomenal consciousness explains the value of our experiences or our lives, and the moral value of beings who are conscious, is less well-grounded than is commonly thought. A great deal of what matters to us and about us can be explained by functional and representational properties that may not be sufficient for phenomenal consciousness. I conclude with some reflections on how these claims might affect debates in ethics.